2005
DOI: 10.1248/bpb.28.584
|View full text |Cite
|
Sign up to set email alerts
|

The Hyperresponsiveness of W/Wv Mice to Oral Sensitization Is Associated with a Decrease in TCR.GAMMA..DELTA.-T Cells

Abstract: The number of patients with food allergies has been increasing for various reasons (e.g., changes in diet, increased stress, etc.), but the mechanisms of the development and regulation of food allergy have not yet been fully elucidated. Thus, oral sensitization models in animals are important for better understanding the induction and regulation mechanisms of food allergy. [1][2][3] When the allergenicity of dietary proteins is evaluated in animal, it is desirable to perform the sensitization orally, preferabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…It is worth noting that the cocoa diet increased the proportion of TCRγδ + and NK cells in three intestinal compartments (mesenteric lymph nodes, PP, and IEL), suggesting their role in the tolerogenic process. In line with this, unripe apple polyphenols induced an increase in the proportion of TCRγδ + IEL in association with the inhibition of the development of an oral sensitization model (25), and it was also reported that the reduction of TCRγδ + cells by the anti-TCRγβ antibody favors an oral sensitization in mice (120). Furthermore, NK cells could have regulatory functions contributing to the avoidance of sensitization in line with the reported prevention of allergic disease (121, 122).…”
Section: Effect Of Cocoa Diet On Antibody-mediated Diseasessupporting
confidence: 55%
“…It is worth noting that the cocoa diet increased the proportion of TCRγδ + and NK cells in three intestinal compartments (mesenteric lymph nodes, PP, and IEL), suggesting their role in the tolerogenic process. In line with this, unripe apple polyphenols induced an increase in the proportion of TCRγδ + IEL in association with the inhibition of the development of an oral sensitization model (25), and it was also reported that the reduction of TCRγδ + cells by the anti-TCRγβ antibody favors an oral sensitization in mice (120). Furthermore, NK cells could have regulatory functions contributing to the avoidance of sensitization in line with the reported prevention of allergic disease (121, 122).…”
Section: Effect Of Cocoa Diet On Antibody-mediated Diseasessupporting
confidence: 55%
“…Furthermore, we have shown that an additional decrease in the percentage of TCRγδ‐T cells in the IEL cells of the W/W V mice was also observed in the orally sensitized W/W V mice [15]. The proportion of TCRγδ‐T cells in the IEL of the W/W V mice reconstituted with bone marrow cells from C57BL/6J increased much more than that in the untreated W/W V mice and further extremely inhibited the development of oral sensitization [25]. These findings suggested that the lowering of the population of TCRγδ‐T cells in the IEL of the W/W V mice could be associated with the high oral sensitivity of the W/W V mice.…”
Section: Discussionmentioning
confidence: 77%
“…Our results are in line with those of Akiyama et al [35], who reported that unripe apple polyphenols inhibit oral sensitization associated with a rise in the proportion of TCRγδ+ IEL. In line with these studies, it was described that a decrease in the number of TCRγδ+ cells induced by anti-TCRγδ antibody treatment facilitated oral sensitization in mice [36].…”
Section: Discussionmentioning
confidence: 85%